Formation of dense non-oxide layer in Al–TiO2–MgO–Al2O3 refractories at 1873 K in flowing N2. Issue 15 (15th October 2019) - Sun, Yang; Li, Yong; Zhang, Lixin; Yan, Mingwei; Ma, Chenhong; Sun, Jialin
Abstract: The dense layer structure in a refractory can enhance its high-temperature service performances. In order to obtain such a structure, the formation, diffusion, and deposition processes of Mg (g) were designed in resin-bonded Al–TiO2 –MgO–Al2 O3 refractory at high temperatures in flowing nitrogen. The AlN–Al2 O3 –MgO ternary system was constructed to obtain the dense layer, which is mainly composed of non-oxides. After being sintered at 1600 °C for 3 h, a dense non-oxide layer was formed in the outer part of the refractory, wherein the outermost part was a granular AlN polytypoid layer, and the remaining positions included Ti(C, N), MgAlONss, and plate-like AlN-polytypoid. The formation of Al3 Ti between Al and TiO2 keeps the refractory in a compact structure during the firing process, and it is finally converted to Ti(C, N). Owing to the formation of Al3 Ti and the dense layer, the apparent porosities of the refractories after being sintered at 1400 °C and 1600 °C are only 2.0% and 5.4%, respectively.